Pengaruh Motivasi terhadap Kinerja Karyawan pada PT. Lika Utama Engineering Medan - Istifany Tri Monica; Ade Rahma Ayu (CIVITAS: Jurnal Studi Manajemen, 2022)
The purpose of this study is to determine whether there was an effect of work motivation on employee performance at PT.Lika Utama Engineering Medan. The sample of this study was 30 employees in 2019, sampling technique used was saturated sampling technique,which was a sampling technique in which all members of the population were sampled. Data analysis was using Simple Linear Regression test, hypothesis test was used coefficient determination test (R2), partial test (t test), while data was processed used SPSS 22. The results of this study showed that work motivation does have a variable on employee performance, other than that,work motivationvariables partialy have no effect and does not significantly affect employee performance at PT. Lika Utama Engineering.